A novel malnutrition assessment model predicts the inflammatory storm of relapsed/refractory acute myeloid leukemia following C-type lectin-like molecule-1 chimeric antigen receptor T therapy - Zhang, Tao; Li, Mengnan; Zhang, Xiaomei; Zhao, Mohan; Jiang, Yanyu; Wang, Xin; Zhao, Yifan; Shi, Xiaoxue; Qu, Wentao; Zhang, Yu; Bai, Xue; Wang, Bing; et al. (Frontiers in Nutrition, 2025)
ObjectivesPrevious studies have been insufficient in addressing malnutrition in leukemia patients and inflammatory storms following immunotherapy infusion. This study investigates the relationship between malnutrition and inflammatory storm after C-type lectin-like molecule-1 chimeric antigen receptor T (CLL1 CAR-T) infusion in relapsed/refractory acute myeloid leukemia (r/r AML) patients.MethodsIn this single-center study, we adopted Controlling Nutritional Status (CONUT) and modified Controlling Nutritional Status (mCONUT) to assess the patient’s malnutrition status. The score of CONUT/mCONUT and the severity and grading of cytokine storm at different time points were collected. The area under the receiver operating curve (AUC) was used to evaluate the malnutrition score to predict the early inflammatory storm after CLL1 CAR-T infusion.ResultsHigher malnutrition scores were significantly associated with increased severity of cytokine release storm (CRS). On Day + 7 and Day + 14 after CLL1 CAR-T infusion, the prediction efficiency of the malnutrition assessment model was high, AUC was greater than 0.8, and CONUT Day + 7 reached the peak (AUC = 0.813), and CONUT Day + 14 (AUC = 0.8009). mCONUT Day + 7 reached the peak (AUC = 0.821), and mCONUT Day + 14 (AUC = 0.8162).ConclusionEarly malnutrition assessment models are practical, objective tools for predicting inflammatory storms in relapsed/refractory AML patients undergoing CLL1 CAR-T therapy.